Determinants Of Fertility Stagnation In Jakarta Province (Data Analysis Of Program Performance And Accountability Survey (SKAP) 2019) - Erina Windiany; Tiarlin Rahel Rahel; Anah Sugihanawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
The Total Birth Rate or Total Fertility Rate (TFR) is an important and strategic indicator to determine the success of a country or the entire country in controlling its population through the Family Planning program. Efforts made by the government, especially the BKKBN in reducing the TFR in Indonesia, yielded good results with the decline in the TFR in Indonesia in 2017 to 2.4 and has not reached the target of reducing the TFR to 2.1. The impact that will occur, if this stagnation cannot be reduced is the occurrence of a population explosion and has an impact on aspects of the economy, employment, health, and other population problems. The purpose of this study was to determine the relationship between the determinant variables of fertility stagnation in Jakarta. This study used a cross-sectional method with secondary data from the Program Performance and Accountability Survey (SKAP) in 2019. The most determinants to cause stagnation are age 20 and >35 years, women of childbearing age not working and age at first marriage <20 and >35 years. This shows that the problems faced are diverse. It is necessary to enhance cross-sectoral cooperation to increase family planning coverage.